2021
DOI: 10.1111/joa.13482
|View full text |Cite
|
Sign up to set email alerts
|

The relative locations of the supraorbital, infraorbital, and mental foramina: A cadaveric study

Abstract: The purpose of this study is to investigate the applicability of the current surgical guideline stating that the main facial foramina that transmit cutaneous nerves to the face (supraorbital notch/foramen, infraorbital foramen, and mental foramen) are equidistant from the midline in European and Hispanic populations. Previous studies suggest this surgical guideline is not applicable for all ethnicities; however, to our knowledge, no data have been published regarding the accuracy of this guideline pertaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The location of the SOF/SON in relation to the supraorbital margin and the respective cranial points were reported in previous studies [2,3,4,10,13,29]. The different locations of the IOF in relation to the infraorbital margin, borders of the maxilla, and zygomaticomaxillary suture had described in the following studies [1,2,4,6,10,11,17,18,20] as well. Furthermore, researchers had reported variations in the position of the IOF with respect to the upper teeth [15,18,20,22].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The location of the SOF/SON in relation to the supraorbital margin and the respective cranial points were reported in previous studies [2,3,4,10,13,29]. The different locations of the IOF in relation to the infraorbital margin, borders of the maxilla, and zygomaticomaxillary suture had described in the following studies [1,2,4,6,10,11,17,18,20] as well. Furthermore, researchers had reported variations in the position of the IOF with respect to the upper teeth [15,18,20,22].…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, many studies have been devoted to assist solve this issue. Different techniques of measurement have been proposed by many authors to determine the topographic and anatomical features of the facial foramina [4,11,12,13,15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the position of the SF, IF, and MF relative to the midline in Latin Americans was also conducted in comparison with the position of the above foramens in Europeans. As a result of the study, it was found that among all the studied ethnic groups, SF, IF, MF were at a distance of 25.32 mm, 29.57 mm, and 25.55 mm from the midline, respectively [8]. V. O. Kostiuk and O. M. Slobodian using modern anatomical methods studied the distances between SF, IF, MF and to standard landmarks in fetuses and newborns, due to which they established the average values of the above-mentioned parameters in different age periods [11].…”
Section: Discussionmentioning
confidence: 80%
“…During dental procedures, such as cleaning and modeling, doctors must respect the precise working length; otherwise, it could cause damage and/or side effects in the patient. This is mentioned in the study by Hester et al [ 35 ], which states that excessive preparation of the canal and violation of the apical foramen, an opening where blood vessels and nerve endings pass that nourish the dental pulp (soft tissue found inside the tooth), can cause direct physical injury to the mental nerve and paresthesia therein. Consequently, if the doctor does not corroborate the presence of this anatomical variant, and if the patient presents with it, it could cause the damage mentioned above and also cause damage to an accessory branch of the nerve, overestimating the symptoms and complications of the treatment.…”
Section: Clinical Considerationsmentioning
confidence: 99%